Penerapan Metode Resitasi pada Mata Pelajaran Akidah Akhlak di MI Darul Falah Konawe - Muhammad Wahab Hadiqi; Muh. Ilham Oihu; Nurlathifah Thulfitrah B. (Lembaga Yasin AlSys, 2026)
Akidah Akhlak instruction at MI Darul Falah Konawe remains dominated by a teacher-centered approach, resulting in students’ active participation and independence not yet developing optimally. This study aimed to describe the application of the recitation method in Akidah Akhlak instruction and to analyze its contribution to students’ understanding and practice of the values of faith and morality. This study employed a qualitative approach with a descriptive design. The research informants consisted of an Akidah Akhlak teacher and students at MI Darul Falah Konawe. Data were collected through observation, interviews, and documentation and were subsequently analyzed using the Miles and Huberman model, which comprises data reduction, data display, and conclusion drawing. The results showed that the recitation method was implemented through three stages: task assignment, task completion, and task accountability. At each stage, students were encouraged to seek, process, and present information related to Akidah Akhlak material, enabling the learning process to become more active and meaningful. The application of the recitation method contributed positively to the development of students’ active participation, independence, responsibility, critical thinking skills, and understanding of Akidah Akhlak material. This study concludes that the recitation method constitutes a relevant learning alternative for improving the quality of the Akidah Akhlak learning process while supporting the development of students’ religious character at MI Darul Falah Konawe. These findings provide practical implications for teachers in designing task-based learning that promotes students’ active participation, responsibility, and independence.